Exploring Maternal Decision-Making in Childbirth at a County Referral Health Facility in Kenya - Waweru, Faith; Muchiri, Eric; Mutema, Alfred (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Choices of childbirth method by women have emerged as a global subject of interest to many health care providers especially considering the steady increasing rate of caesarean sections (CS), and with some countries exceeding the World Health Organization (WHO) recommendation of 10-15%. With increased access to health facilities for maternal childbirth in Meru County, it was important to understand the factors that influence the choice of delivery method by women attending antenatal care. The aim of this study was to determine the factors associated with choice of child delivery methods in Meru Level V Hospital. A cross- sectional study of 300 expectant mothers attending ANC were interviewed and data analyzed using SPSS. The mean age of participants was 28.6±5 years (19 - 42 years). Majority of women in the study had over 12 years of Education (Tertiary Education – 73%) and only 2% had Primary level education. The most prevalent method of childbirth was vaginal delivery, accounting for 53% of cases, while the rate of Cesarean section (CS) deliveries had increased compared to previous years. The decision-making process for choosing the delivery method was influenced by factors such as the social status of women and the fear of pain during delivery. The level of education for women played a role in the decision, with considerations such as knowledge of infection risk, maternal complications, healing time, and cost impacting the choice between natural delivery and CS. several significant factors were identified as contributing to the choice of delivery method, including the influence of relatives, past childbirth experiences, and information obtained from media sources. In conclusion, the decision-making process for childbirth is influenced by a combination of knowledge, attitudes, and social factors among women attending antenatal care at Meru Level V Hospital.